3D-Reconstructions and Re-production in Archaelogy - Ioannides, Marinos; Wehr, Aloysius (My University, 2002)
First an imaging 3D-Laser Scanner (3D-LS) will be presented and its functioning will be explained. The scanning mechanism of the3D-LS is realized by two Galvanometer Scanners. Using such a scanning device it is possible to program various scanning patternsdepending on the application. Therefore, the scanner can be applied for the digitization of small sculptures as well as for digitizinginteriors of rooms. It has been shown that the 3D-LS is an excellent tool for 3D-Reconstruction. However, using laser scanners fordigitizing comprehensively archaeological items means that several hundreds of Megabytes must be efficiently processed. Thisproblem will be addressed in the second part. It will be shown, how laser scanner data must be processed to obtain NC-programs forre-production in archaeology. Here the Advanced Surface Modeling Software Package (ASMOS) developed by the University ofStuttgart and the Higher Technical Institute is applied. Also the problem reconstructing solids by using 3D-LS data from differentoverlapping views will be addressed and examples will be presented. Various examples will demonstrate that 3D-LS can be wellapplied in 3D-reconstruction and re-production if sophisticated and powerful software packages are available for processing the 3D-LS image data efficiently.
Keywords: Imaging 3D-laser Scanning; CW-laser; Scanning Geometry; 3D-digitization; 3D-Reconstruction; Point cloudsprocessing; CAD-modeling; Reverse Engineering; Cultural HeritageRecording